Peran Pemerintah Kota Medan dalam Menjamin Kesejahteraan Penyandang Disabilitas - Yusuf Hanafi Siregar; Sismudjito Sismudjito; Bengkel Ginting (PERSPEKTIF, 2023)
The purpose of this research article is to find out the role of the Medan City government in ensuring the welfare of persons with disabilities, the efforts that have been realized by the Medan City government in ensuring the welfare of persons with disabilities and the obstacles found by the Medan City government in ensuring the welfare of persons with disabilities. In Indonesia, all access and empowerment for persons with disabilities are still not effective. This is evident from the lack of provision of public facilities for persons with disabilities, schools or non-formal education for persons with disabilities, empowerment from the government or other agencies as well as periodic social assistance. This research uses a qualitative descriptive research type. Data collection techniques were carried out using observation, interviews and literature studies. The results of this study explain that the role of the Medan City Government through the Social Service in the welfare of persons with disabilities consists of four aspects, namely: the aspect of the facilitator by purchasing and providing assistive facilities and distributing them to persons with disabilities who have been recorded every month. The regulatory aspect of the efforts being made is implementing all the rules and policies based on the Ministry of Social Affairs Regulation Number 2 of 2021 concerning persons with disabilities. From the point of view of the caalitator inviting social problem institutions such as PSM (Community Social Worker), PKSK (District Social Welfare Worker) and TKSPD (Social Welfare Workers for Persons with Disabilities) and the obstacle encountered is the limited budget funds to buy auxiliary equipment facilities, only 75 units each months, there is a quota (limit) for receiving direct cash assistance and there is no Regional Regulation or Medan City Mayor Regulation regarding persons with disabilities